2009
DOI: 10.1248/bpb.32.1235
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis and Chemical Evaluation of Ephedra Plants in Mongolia

Abstract: Ephedrae herba has been used in traditional Chinese and Japanese (Kampo) medicine from ancient times, with the primary resource being in China. In the present study, a field survey as well as molecular and chemical assessments were conducted on Ephedra plants in Mongolia to clarify whether they could be an alternative resource of the Ephedrae herba used in Japanese Kampo medicine. Ephedra sinica, E. equisetina, E. przewalskii, E. regeliana, E. monosperma and an unknown taxon (ESP) collected in Mongolia were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 14 publications
2
48
0
Order By: Relevance
“…In our previous paper, 1) we reported that additive peaks at the nucleotide position 1709th of 18S rRNA gene sequences were observed in most samples of E. sinica and Epheda sp., with variable relative-intensity between the two peaks. However the additive peaks, sometimes with a weak signal of the 2nd peak, were difficult to distinguish from high noise sites.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…In our previous paper, 1) we reported that additive peaks at the nucleotide position 1709th of 18S rRNA gene sequences were observed in most samples of E. sinica and Epheda sp., with variable relative-intensity between the two peaks. However the additive peaks, sometimes with a weak signal of the 2nd peak, were difficult to distinguish from high noise sites.…”
mentioning
confidence: 79%
“…In order to search for alternative resources in neighboring regions, we carried out field investigations on Ephedra plants in Mongolia during 2002Mongolia during -2004, and subsequently conducted molecular and chemical evaluations. The results 1) revealed that E. sinica and E. equisetina in eastern and central Mongolia had potential as new resources of Ephedrae herba of JP grade, and other species could be resources of ephedrine alkaloids.However, during those investigations, we found that many Ephedra populations in the southern area had curved or twisted stems and were therefore very difficult to identify from external features. We treated them tentatively as Ephedra sp., and successive molecular analysis suggested hybrid origins of these plants.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Ephedrine activates the central nervous system, increases blood pressure, dilates the bronchial tubes, and increase the pulse rate. Pseudoephedrine is used for the relief of nasal congestion in its synthetic form (17)(18)(19). The herb Ephedra, or ma-huang as the aerial part of the herb is identified in conventional Chinese medicine, is the oldest medicinal herbs mentioned in literature.…”
Section: Introductionmentioning
confidence: 99%